Disease severity and family history in keratoconus. Issue 8 (24th July 2008) - Szczotka-Flynn, L; Slaughter, M; McMahon, T; Barr, J; Edrington, T; Fink, B; Lass, J; Belin, M; Iyengar, S K
Abstract : Background/aims: To determine if disease severity is associated with a family history of keratoconus. Methods: Markers of disease severity in the CLEK Study cohort were assessed to determine if they could discriminate individuals with and without family history. Logistic regression was used to examine association between corneal scarring, average corneal power, flat and steep keratometry readings, and higher-order root mean square (RMS) wavefront error with family history. Results: In univariate analyses, none of the severity indices had any significant associations with family history; however, contact lens use, gender, and Caucasian race were found to be significant predictors. After controlling for these confounders, there were no significant associations between any severity indices and family history. Conclusions: Presence or absence of family history is not associated with more severe clinical disease, at least when each marker for severity is considered independently. The results of this analysis are important for genetic studies of keratoconus in that it will allow recruitment of keratoconus patients across all stages of disease severity because it does not influence familial aggregation.